O Mercosul na visão retórico-discursiva dos editoriais dos jornais Gazeta do Iguaçu (BR) e Vanguardia (PY) - Nunes Neto, Carmen Aparecida (2012)
Whereas the Editorial is the text that expresses the opinion of a newspaper, this study analyzes the thesis and the particular arguments of this kind of newspapers Gazeta do Iguaçu and Vanguardia published in Foz do Iguaçu (Brazil) and Ciudad del Este (Paraguay), respectively. It aims to realize and understand the extent to which the integration were be occurring, according to the political position - for or against of each one of the newspapers. Therefore examines the technical arguments and sensitizers from the theoretical and methodological assumptions of the Rhetorical Theory of Speech - TRD of Dittrich (2008) with the support of Perelman-Tyteca s Theory of Argumentation (2005). The analyses are developed by comparing the thesis and arguments of each Editorial in 10 newspaper published during the year 2010, selected by a theme relating to Mercosul. The study indicates that, in general, the position of Paraguayans Editorials compliance is contrary to th e principles of Mercosul, while the Brazilian Editorials stand with greater restraint in this regard.